Dynamic tuning of parallel/distributed applications - Morajko, Anna (2004)
The thesis addresses the problem of automatic and dynamic tuning of parallel and distributed applications. Our objective is to help developers in the process of improving the application performance. The work presents a whole solution that deals with the issues of automatic and dynamic application improvement. In this approach, an application is monitored, its performance bottlenecks are detected, solutions are given and the application is modified on the fly